In Vivo Anti-inflammatory, Analgesic, and Sedative Studies of the Extract and Naphthoquinone Isolated from Diospyros kaki (Persimmon) - Bawazeer, Saud (ACS Omega, 2021)
[Image: see text] Anti-inflammatory, analgesic, and sedative medicine is used with numerous side effects, including peptic ulcer, headache, addiction, and other complications. In this regard, discovery research is undergoing a process to discover effective, safe, and economical drugs with no side effects. The aim of this study was to assess chloroform extracts and isolated compounds for anti-inflammatory, analgesic, and sedative activities in animal models. The anti-inflammatory potential was measured by using the carrageenan-induced and histamine-induced paw edema procedure, while the analgesic potential was determined using a hot plate analgesiometer. The sedative effect was observed in an animal model for screening of the locomotor effect of the extract and isolated compound 1. Our data exhibited that the extract and compound 1 attenuated carrageenan-induced and histamine-induced paw edema (93.98 and 89.54%, respectively). Furthermore, compound 1 attenuated biphasic edema associated with histamine and prostaglandins. The chloroform extract showed a moderate analgesic effect; however, compound 1 showed a significant analgesic potential (p < 0.001) by increasing the latency time of the animals in the thermally induced algesia model. Compound 1 exhibited a significant sedative effect and dose-dependent analgesic activity. It is concluded that the chloroform extract and compound 1 showed remarkable anti-inflammatory, analgesic, and sedative activities. This research work strongly rationalizes the folkloric usage of Diospyros kaki in the treatment of inflammation, pain, and insomnia.